The Effectiveness Of Siganta Games In Improving Knowledge Of First Aid In Accidents And Emergencies - hafiz, jihan fadilla; Khasanah, Furaida; Laasara, Nurun; Maryana (International Conference on Health Sciences, 2026)
Background: Accidents in school environments can occur suddenly and lead to injuries or emergencies requiring immediate treatment. First aid knowledge is essential for all school members, but the education provided so far has been limited in terms of both content and scope. Innovative learning media such as the SIGANTA educational game are one alternative for improving students' knowledge interactively. Objective: This study aims to determine the effectiveness of the SIGANTA game as an educational medium for improving first-aid knowledge of accidents and emergencies at SMPN 3 Banguntapan. Method: This study employed a quasi-experimental design with a pretest-posttest control group design. A total of 200 seventh-grade students were randomly assigned to an intervention group (SIGANTA game-based education) and a control group (leaflet education). Data collection used a first aid knowledge questionnaire that had been validated and reliability-tested. Data analysis was conducted using the Wilcoxon Signed-Rank Test and the Mann-Whitney Test at a significance level of p<0.05. Results: Before the intervention, most students in both groups had low levels of knowledge. After the education, the intervention group showed a significant increase in the good knowledge category (47%), while the control group only reached 23%. There was a significant difference in posttest scores between the intervention and control groups (p=0.000). Conclusion: The SIGANTA game is an effective educational medium for improving knowledge of first aid in accidents and emergencies at school. The integration of interactive learning media into school health education is recommended to enhance students' preparedness to handle emergencies.